2003
DOI: 10.1186/1471-5945-3-3
|View full text |Cite
|
Sign up to set email alerts
|

CD1a expression in psoriatic skin following treatment with propylthiouracil, an antithyroid thioureylene

Abstract: BackgroundThe antithyroid thioureylenes, propylthiouracil (PTU) and methimazole (MMI), are effective in the treatment of patients with plaque psoriasis. The mechanism of action of the drugs in psoriasis is unknown. Since the drugs reduce circulating IL-12 levels in patients with Graves' hyperthyroidism, the effect of propylthiouracil on CD1a expression in psoriatic lesions was examined in biopsy samples of patients with plaque psoriasis. CD1a is a marker of differentiated skin antigen presenting cells (APC, La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
(33 reference statements)
2
6
2
Order By: Relevance
“…Furthermore, various non‐retinoid drugs have shown to promote similar outcomes in epidermal thickness, 26,29–33,39 epidermal inflammation, 29,32,39 CK10 positivity, 7,34 CK16 positivity 27,29,30,33,39 and Ki67 positivity 7,29,30,32,34,39 . However, there are only two studies comparing the amount of Langerhans’ cells in epidermis before and after anti‐psoriatic treatment using CD1a as marker 32,35 . Whereas the present study showed decrease in number of CD1a‐positive cells after treatment with acitretin, that result being similar to what Asadullah et al 32 found with systemic IL‐10 therapy, Elias et al 35 did not notice any difference after treatment with propylthiouracil.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, various non‐retinoid drugs have shown to promote similar outcomes in epidermal thickness, 26,29–33,39 epidermal inflammation, 29,32,39 CK10 positivity, 7,34 CK16 positivity 27,29,30,33,39 and Ki67 positivity 7,29,30,32,34,39 . However, there are only two studies comparing the amount of Langerhans’ cells in epidermis before and after anti‐psoriatic treatment using CD1a as marker 32,35 . Whereas the present study showed decrease in number of CD1a‐positive cells after treatment with acitretin, that result being similar to what Asadullah et al 32 found with systemic IL‐10 therapy, Elias et al 35 did not notice any difference after treatment with propylthiouracil.…”
Section: Discussionsupporting
confidence: 88%
“…There are many studies comparing histological and immunohistochemical aspects of psoriasis before and after treatment with several drugs 7,26–36 . However, there are three studying psoriasis before and after retinoid therapy under the same scope 16,23,37 among which only one has acitretin as one of the elected drug 16 …”
mentioning
confidence: 99%
“…Psoriasis is an autoimmune‐mediated disease where T cells activated by mature Langerhans cells play a pivotal role in the pathogenesis of the disease. Histopathological key phenomena in the psoriatic plaque are accumulation of T‐cell subsets and epidermal hyperproliferation with premature keratinization 10–12 . In the present study, however, immunoreactivity of makers of differentiation (involucrin) and proliferation (Ki‐67) did not differ significantly between the treatment modalities, indicating that at 6 weeks both treatments do not appear to be substantially different in influencing the differentiation and proliferation status of psoriasis.…”
Section: Discussioncontrasting
confidence: 66%
“…However, taken together with our current study, these studies may also show a pleiotropic effect of IL-1Rrp2 and its ligands on different cells and it is not known what the effect of these cytokines have on Langerhans cells or epidermal DCs in the skin, which are phenotypically similar to MDDCs [21,22]. One study has shown that Langerhans cells act to dampen skin inflammation [29] and another study has shown that Langerhans cell recruitment is increased in the skin of psoriatic patients successfully treated with propylthiouracil, which has anti-inflammatory properties [30]. The potential of IL-1 cytokines for immunomodulatory therapies has previously been reviewed by Dumont [31].…”
Section: Discussionmentioning
confidence: 99%